InRaDoS: An internal radiation dosimetry computer program - Alireza Sadre Momtaz; Sheikhangafsheh, Farzin Safarnejad (Majallahī-i pizishk-i hastahī Īrān, 2021)
Introduction: Internal radiation dosimetry is important from a radiation protection point of view and can help to optimize the radiation dose delivered to the workers, public, and patients. It has a rather simple protocol but needs a large amount of data. Therefore, it is difficult to do on a routine basis. The use of computer programs makes internal radiation dosimetry simpler and less time consuming and also decreases the possibility of human errors. Methods: The photon’s specific absorbed fractions for two versions of Oak Ridge National Laboratory phantoms were calculated using MCNPX code and a Python code was used to calculate the S-values for selected radionuclides. Then calculated S-values transferred to an excel spreadsheet. The program’s GUI was developed with the Tkinter module of Python programming language. Results: A user-friendly program for internal radiation dosimetry was developed using Python programming language. This program allows the user to calculate the absorbed dose for 20 source organs in 23 target organs for two phantoms. Also, it is possible to compare the results of the two phantoms. Originally, 40 radionuclides were included in the program. Conclusion: This program can be a useful tool for the assessment of organ absorbed doses for individuals dealing with radiation such as patients and workers. It decreases the time of dose calculation and helps to avoid human mistakes.